EURÍPIDES Y LA MÚSICA DEL DRAMA ÁTICO: UNA REVISIÓN DEL PAPIRO DEL ORESTES - Redondo Reyes, Pedro (Myrtia, 2001)
In this paper I outline a revision of greek music development, with special regard to Euripides and the so called Orestes Papyrus . Next, I expound the musical problems of this papyrus and its relation to greek music theory. Finally, I try to look at a possible authorship for it.